Penciptaan Video Seni “Panji Romance” - Didit Prasetyo Nugroho (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2019)
The story of Panji is an oral literature that tells the story of the love story of Raden Panji Asmarabangun, a crown prince of the Kingdom of Jenggala, with Dewi Sekartaji, a princess of the Kingdom of Panjalu. The romantic journey of the two characters did not go smoothly, but there were many adventures and disguises so that the story of Panji spread with various versions in the form of fairy tales and other folk tales. Panji's story is displayed in the form of literary and performing arts. This story also appears in various versions. The differences in the version are generally caused by the personal creativity of the adapters, the flexibility of the story in the form of oral traditions, and the adaptation of stories to myths and legends in each area of ​​its distribution. Of the various types of stories performed by various regions, Malang is one of the regions that has a distinctive artistry, Malang puppet mask. Puppet mask is a performance of the type of drama that emphasizes the aspects of dance as its main presentation and mastermind as the organizer of the story. Each dancer wears a mask that differs according to the character he plays. Malang wayang topeng art has become an art that has been inherent in the Malang community since long ago and has become part of the identity of the Malang community. In this study, the author describes how the process of designing art videos is based on Malang puppet mask stories under the title